Copper‐Catalyzed Trifluoromethylation of Trisubstituted Allylic and Homoallylic Alcohols. Issue 18 (24th March 2015) - Lei, Jian; Liu, Xiaowu; Zhang, Shaolin; Jiang, Shuang; Huang, Minhao; Wu, Xiaoxing; Zhu, Qiang
Abstract An efficient copper‐catalyzed trifluoromethylation of trisubstituted allylic and homoallylic alcohols with Togni's reagent has been developed. This strategy, accompanied by a double‐bond migration, leads to various branched CF3‐substituted alcohols by using readily available trisubstituted cyclic/acyclic alcohols as substrates. Moreover, for alcohols in which β‐H elimination is prohibited, CF3‐containing oxetanes are isolated as the sole product.